Exploring the behavior of solitons on a desktop personal computer - López-Aguayo, S.; Ochoa-Ricoux, J.P.; Gutiérrez-Vega, J.C. (Revista Mexicana de Física E, 2006)
In recent years, there has been a growing interest in studying and applying nonlinear wave equations and their soliton solutions. In this paper we discuss at undergraduate level a simple finite--difference numerical method for solving nonlinear wave equations. This method is applied for studying the striking behavior of the optical solitons. The procedures presented can be reproduced by enthusiastic students and instructor with a minimum of programming experience. We provide a set of interesting problems that could be taken as starting point to numerically explore the solutions of nonlinear wave equations.